Golden Helix or Tangled Web? The Impact of Patent Strategy on the Long-Run Supply of Public Knowledge - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2008)
Firms using knowledge for competitive advantage seek to incorporate ideas from public knowledge stream into their private, patented knowledge streams. While management scholarship focuses on improving the link from public to private knowledge streams, policy literature suggests firm patents reduce public knowledge stream. This is particularly salient in genomics where patenting has exploded but its impact on public knowledge remains controversial. Using gene patent-paper pairs, we find patent grant impedes follow-on public knowledge production by 5 to 17%, exacerbated by patent thickets, ownership fragmentation, and commercial relevance. This suggests aggressive patenting strategies diminish the long-run supply of public domain knowledge.